Community Empowerment and Social Welfare Development through Social Entrepreneurship - Yerik Afrianto Singgalen; Rosdiana Sijabat; Pristiana Widyastuti; Agnes Harnadi (Jurnal Studi Sosial dan Politik, 2022)
Social entrepreneurship is an alternative approach to improving social welfare through community empowerment programs. In the Indonesian context, Yayasan Cinta Anak Bangsa (YCAB) and Cinderella Indonesia Foundation (CIF) have essential roles in improving marginalized communities' social welfare. Considering this, it is necessary to conduct a comprehensive study of institutional and leadership dimensions related to the social entrepreneurship approach. This research uses qualitative methods through a case study approach. Data was collected through in-depth interviews with key informants, namely the initiators or founders of YCAB and CIF. Document studies were conducted to understand the organizational profiles. Furthermore, the processing of research data uses triangulation techniques to obtain credible and valid information so that it can be used to reconstruct research thinking ideas related to community and social development from an institutional and leadership perspective in the field of social entrepreneurship. These research findings indicate that Yayasan Cinta Anak Bangsa (YCAB) and Cinderella from Indonesia Center have established partnerships with various parties for collaborative advantages. Thus, Social enterprise plays a vital role in community development and mobilizes the capabilities to maintain livelihoods and improve social welfare.